Inquiry-Based Learning in Cooperative Economics: Examining Cognitive and Affective Learning Responses - Yuliana FH; Shewa Seyoum (Universitas Negeri Semarang, 2026)
This study examines how Inquiry-Based Learning (IBL) shapes student learning responses within undergraduate economics teacher education, specifically in cooperative economics courses. Drawing on constructivist learning theory and active learning literature, the study explores cognitive, affective, and behavioral dimensions of student responses to IBL implementation. Adopting a mixed-method descriptive design, qualitative data were obtained through classroom observations, semi-structured interviews, and document analysis involving 32 students in the Economics Education Study Program at Universitas Sriwijaya. Quantitative support was derived from a structured observational rubric measuring participation, inquiry engagement, and learning autonomy, generating an overall responsiveness score of 85.51%. The findings indicate consistently positive student responses, reflected in stronger engagement, deeper conceptual comprehension, and enhanced self-directed learning. By evidencing how inquiry-oriented pedagogy fosters meaningful learning beyond transmissive instruction, this study contributes to the expanding discourse on student-centered approaches in economics education. The results provide pedagogical implications for strengthening critical and reflective engagement in cooperative economics within emerging higher education contexts, particularly in preparing future economics teachers.